From policy to practice: Empowering African languages in South African higher education - Maponopono, Naledi (Journal of International Students, 2026)
This study examines the role of African languages in South African higher education, highlighting the intersection of language policy, identity, and equity. Despite progressive language policies promoting multilingualism, English remains the dominant medium of instruction, creating barriers for both local and international students. Using Ruiz’s (1984) Language Orientations Framework and Barkenbus’s Four-Stage Policy Model, this study investigates the policy-practice gap in the implementation of African languages at the University of Cape Town (UCT). The findings reveal institutional, pedagogical, and ideological barriers hindering effective multilingual education. The paper argues that the marginalization of African languages contributes to epistemic injustice and proposes strategies to enhance linguistic inclusivity, including translanguaging pedagogies, policy enforcement mechanisms, and the development of African-language instructional resources.  The study contributes to intersectional language studies by exploring how linguistic hierarchies shape access and identity in higher education for both local and international students.